Establishing a university-wide culture on sustainability by developing sustainability change agents: lessons from Stellenbosch University’s listen, live and learn (LLL) initiative - Langa, Zamokuhle Vanessa (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScFoodSc)--Stellenbosch University, 2021.